Hackathon as a Project Based Teaching Tool : Employing Programming Challenge in the Class - Kumalakov, Bolatzhan; Kim, Alla; Mukhtarova, Salima; Shukurova, Assel; Khon, Natalya (International Conference on Application of Information and Communication Technologies, 2018)
Project Based Learning (PBL) develops student knowledge and skills through solving authentic, engaging and complex challenge in a fixed time span. Academic literature reports its application over a wide variety of disciplines, having both immediate and long-lasting positive effect on team working, project management, and creativity when applying technical skills. We aim to enhance student learning in software engineering. 80% of student respondents up to the date feel that programming assignments that last longer than a week overlap with other subjects enough to draw dedication away. While it unquestionably develops transferable skills, such as time management, it also might not necessarily be good through introductory courses, where students face completely new material. As a result, our aim is to employ "hackathon" - a gathering, where programmers collaboratively code in an extreme manner over 12 to 24 hours - as a teaching tool. While there is a precedent of hackathon being used at University level, it was employed to substitute classic approach via excluding lecturing and lab work completely. Current paper presents research design and relevant discussion on measuring and validating learning outcomes when blending hackathon into traditional programming class as one of the components, not a substitute to other types of classes.